Fundamentals of investment management - Hirt, Geoffrey A.; Block, Stanley B. (Dubuque : McGraw-Hill/Irwin, 2012)
'Many changes have taken place in the financial markets since the first edition of Fundamentals of Investment Management was published in the early 1980s. However, the one constant has been a sincere commitment within this text to capture the excitement and enthusiasm that we feel for the topic of investment management. Throughout the book, we attempt to present applied theory alongside real-world examples that illustrate the theory. Our goal is that by the time conscientious students complete an investment class using this textbook, they will be able to manage investments in the real world. We approach financial analysis the way it is done by many Wall Street firms. Geoff Hirt directed the CFA program for the Investment Analysts Society of Chicago (now the CFA Institute of Chicago) for 15 years and sat on the board of directors from 2002 to 2005. Stan Block has been a practicing CFA for over 20 years. Both of us have taught and advised student-managed investment funds at our universities and we bring this wealth of learning experience to the students who study from this text. Both of us manage diversified portfolios. We are close to the markets on a daily basis and keep abreast of major developments in the economy, market structure, and globalization of the markets. Above all else, we have written a text that is user-friendly, but make no concessions to the importance of covering the latest and most important material for the student of investments'--
Machine generated contents note: Part One: Introduction to InvestmentsChapter 1: The Investment SettingChapter 2: Security MarketsChapter 3: Participating in the MarketChapter 4: Investment Companies: Mutual Funds, Exchange-Traded Funds, Closed-End funds, and Unit Investment TrustsPart Two: Analysis and Valuation of Equity SecuritiesChapter 5: Economic ActivityChapter 6: Industry AnalysisChapter 7: Valuation of the Individual FirmChapter 8: Financial Statement AnalysisPart Three: Issues in Efficient MarketsChapter 9: Efficient Markets and AnomaliesChapter 10: Behavioral Finance and Technical AnalysisPart Four: Fixed-Income and Leveraged SecuritiesChapter 11: Bond and Fixed-Income FundamentalsChapter 12: Principles of Bond Valuation and InvestmentChapter 13: Convertible Securities and WarrantsPart Five: Derivative ProductsChapter 14: Put and Call OptionsChapter 15: Commodities and Financial FuturesChapter 16: Stock Index Futures and OptionsPart Six: Broadening the Investment PerspectiveChapter 17: A Basic Look at Portfolio Management and Capital Market TheoryChapter 18: Duration and Bond Portfolio ManagementChapter 19: International Securities MarketsChapter 20: Investments in Real AssetsChapter 21: Alternative Investments: Private Equity and Hedge FundsChapter 22: Measuring Risks and Returns of Portfolio ManagersAppendicesAppendix A: Compound Sum of $1Appendix B: Compound Sum of an Annuity of $1Appendix C: Present Value of $1Appendix D: Present Value of an Annuity of $1Appendix E: Time Value of Money and Investment ApplicationsAppendix F: Using Calculators for Financial Analysis.
Includes bibliographical references and index.
Keywords: Investments; Investments -- United States; Investment analysis